Therapy of Endogenous Thrombolysis with Dietary Natto Based on Inferior Local Beans in Atherogenic Rat (Rattus Norvegicus) Model - Kholis, Nur; Yanti, Veni Ardini Dewi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
Natto is a fermented food from soybean that produce nattokinase enzyme with high thrombolitic activity. Soybean as raw material for making natto, however is a kind of superior bean which is 68% of national necessary come from imported soybean. Therefore, we need to explore the potency of inferior local beans i.e. brown cowpea, white cowpea, and â€œkomakâ€ bean as soybean substitute for making natto. The aim of this research was to study the effects of using inferior beans as substrate of natto fermentation on in vivo thrombolytic activity. The result showed that diet of natto from inferior beans were significantly different (P<0.05) on decreasing of serum cholesterol, serum MDA (malonaldialdehide), foam cell of aorta, and on increasing of endothelial cell of aorta compared to atherogenic rats group without natto diet. However, it was not significantly different (P>0.05) on all parameters compared to soy-natto diet (product control). It means that inferior beans were able to substitute soybeans as raw material for making a functional natto. White cowpea natto showed the best thrombolytic activity in atherogenic rats among other inferior beans with the highest nattokinase activity of 86.4 FU/g.Keywords: thrombolysis therapy, natto, inferior beans, atherogenic rat